Electronic and Photonic Packaging, Electrical Systems and Photonic Design, and Nanotechnology 2003
DOI: 10.1115/imece2003-41892
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Experimental Shock and Impact Response Data of a Printed Wire Board

Abstract: There is considerable reported evidence that a large percentage of portable electronics product failure is due to impact or shock during use. Failures of the external housing, internal electronic components, package-to-board interconnects, and liquid crystal display panels may occur as the result of dropping. For many orientations of drop, the Printed Wire Board (PWB) will flex significantly during the impact event and subsequent clattering. Reducing the curvature and acceleration of the PWB during impact is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The technique was demonstrated for boards mounted with thin profile fine pitch ball grid array (TFBGA) and very thin profile fine pitch ball grid array (VTFBGA) components. In November 2003, Heaslip and Punch [14] demonstrated the use of wavelet analysis to understand the complex spectral response of an unpopulated board subjected to drop tests. In 2004, Zhu and Marcinkiewicz [15] proposed the use of effective plastic strain in the solder ball as the damage metric and compared the component reliability at different loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The technique was demonstrated for boards mounted with thin profile fine pitch ball grid array (TFBGA) and very thin profile fine pitch ball grid array (VTFBGA) components. In November 2003, Heaslip and Punch [14] demonstrated the use of wavelet analysis to understand the complex spectral response of an unpopulated board subjected to drop tests. In 2004, Zhu and Marcinkiewicz [15] proposed the use of effective plastic strain in the solder ball as the damage metric and compared the component reliability at different loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Xue et al 19 analyzed the effect of the band geometry and materials on the dynamic response of a guided projectile during the engraving process. With the theory of wavelet and by the means of finite element analysis (FEA), Heaslip and Punch 20 reduced the failure of devices in projectiles with a foam material; however, this method may affect the upgrade and replacement for the system. Chakka et al 21 used carbon fibers embedded in an epoxy matrix and studied the effect of reducing the transmitted shocks during launch with the composite supporting plate by varying the thickness of it.…”
Section: Introductionmentioning
confidence: 99%
“…Heaslip and Punch [3] concluded that there is considerable evidence to suggest that a large percentage of portable electronic products fail due to impact or shock during use. Some of the electronic component failure problems can be reduced by enclosing the components within foam.…”
Section: Introductionmentioning
confidence: 99%
“…Contractors used the peak values to perform static analysis and quasi-static in centrifuge tests. The dynamics of the projectile structure [3], particularly during the muzzle exit transient, were usually neglected. As a result, programs like the US Army's Excalibur and SADARM experienced numerous failures of sensitive equipment during the early stages of development.…”
Section: Introductionmentioning
confidence: 99%